Design and Fabrication Challenges of a Highly Sensitive Thermoelectric-Based Hydrogen Gas Sensor - Anmona Shabnam Pranti; Daniel Loof; Sebastian Kunz; Volkmar Zielasek; Marcus Bäumer; Walter Lang (Micromachines, 2019)
This paper presents a highly sensitive thermoelectric sensor for catalytic combustible gas detection. The sensor contains two low-stress (+176 MPa) membranes of a combination of stoichiometric and silicon-rich silicon nitride that makes them chemically and thermally stable. The complete fabrication process with details, especially the challenges and their solutions, is discussed elaborately. In addition, a comprehensive evaluation of design criteria and a comparative analysis of different sensor designs are performed with respect to the homogeneity of the temperature field on the membrane, power consumption, and thermal sensitivity. Evaluating the respective tradeoffs, the best design is selected. The selected sensor has a linear thermal characteristic with a sensitivity of 6.54 mV/K. Additionally, the temperature profile on the membrane is quite homogeneous (20% root mean standard deviation), which is important for the stability of the catalytic layer. Most importantly, the sensor with a ligand (p-Phenylenediamine (PDA))-linked platinum nanoparticles catalyst shows exceptionally high response to hydrogen gas, i.e., 752 mV at 2% concentration.